PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KETERAMPILAN BERPIKIR KRITIS PADA MATERI SISTEM EKSKRESI - Isnaini Hasyim Harahap; Nirwana Anas; Melfa Aisyah Hutasuhut (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
Student worksheet contains various activities that are used to facilitate and practice students' skills in learning activities. This research aims to determine the development of student worksheet based on critical thinking skills that are valid, practical, and effective on the excretory system. This is a research and development of ADDIE model. The validity of student worksheet was measured using a validation sheet. The validity of student worksheet is 78% categorized as valid. Material validity of 82% is categorized as very valid, media validity of 81% is categorized as very valid, and language validity of 71% is categorized as valid. The practicality of the student worksheet was measured using a practitioner validation sheet and student response questionnaires. The practicality of worksheet is 87% categorized as very practical. Based on practitioner validation, the result of worksheet practicality of 89% is categorized as very practical and student response questionnaire of 85% is categorized as very practical. worksheet effectiveness was measured by normalized gain test. The control class N-Gain score of 0.2 is categorized as low and the experimental class N-Gain score of 0.5 is categorized as moderate.Keywords: Effectiveness, Practicality, Critical Thinking Skills, Student Worksheet, Validity.